White poplar (Populus alba L.) - Litter impact on chemical and biochemical parameters related to nitrogen cycle in contaminated soils - Paula Madejon; Lisa Ciadamidaro; Francisco Cabrera; Engracia Madejon (Forest Systems, 2014)
Aim of study: The aim of this study was to determine the effect of litter from Populus alba on chemical and biochemical properties related to the N cycle in soils with different pH values and trace element contents. We hypothesized that this litter would influence several parameters related to the N cycle and consequently to soil health. Area of study: we collected two reforested contaminated soils of different pH values (AZ pH 7.23 and DO pH = 2.66) and a non-contaminated soil (RHU pH 7.19). Materials and methods: Soil samples were placed in 2,000 cm3 microcosms and were incubated for 40 weeks in controlled conditions. Each soil was mixed with its corresponding litter, and soils without litter were also tested for comparison. Ammonium (NH4+-N) and nitrate (NO3–-N) content, potential nitrification rate (PNR), microbial biomass nitrogen (MBN), protease activity, and several chemical properties such as pH, available trace element concentrations (extracted with 0.01 M CaCl2) were determined at different times of incubation. Main results: Values of available trace elements did not vary during the incubation and were always higher in acid soil. In neutral soils litter presence increased values of Kjeldahl-N, NO3–-N content, potential nitrification rate (PNR), microbial biomass nitrogen (MBN) and protease activity. Presence of trace elements in neutral soils did not alter the parameters studied. However, acidic pH and high content of available trace elements strongly affected NH4+-N andNO3–-N, microbial biomass N and protease activity. Research highlights: Our results showed the negative effect of the acidity and trace element availability in parameters related with the N-cycle. Key words: microbial biomass N; protease activity; soil pH; N mineralization; nitrification; phytoremediation.